“OPTIMIZING URBAN LANDSCAPE DESIGN THROUGH TERRAIN, WATER, AND VEGETATION INTEGRATION” - Eshmamatov Xushnudbek Obidjonovich (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article investigates the integration of terrain, water, and vegetation in urban landscape design to improve ecological sustainability, recreational opportunities, and aesthetic appeal. It discusses how natural slopes, hills, valleys, and artificial landforms can organize functional zones, support microclimates, and enhance biodiversity. The study reviews international experiences from Europe and North America alongside local practices in Central Asia, illustrating how terrain and natural elements can be harmonized in urban planning. The findings highlight strategies for creating sustainable, visually engaging, and multifunctional urban landscapes that balance ecological, aesthetic, and social needs.